2017
DOI: 10.1155/2017/3754145
|View full text |Cite
|
Sign up to set email alerts
|

The Anti‐Inflammatory Effects of Invigorating Kidney and Supplementing Qi Chinese Herbal Formulae in Asthma Patients

Abstract: Background The theories of Shen-reinforcement and Qi-supplementation are important in asthma treatment based on traditional Chinese medicine theories. Early studies suggested that Invigorating Kidney and Supplementing Qi herbal formulae, Bu Shen Fang Chuan (BSFC) and Bu Shen Yi Qi (BSYQ), conveyed promising results in asthma treatment. However, the efficacy and safety of the formulae need to be further investigated by a randomized double-blind clinical trial. Methods 328 eligible patients were randomly sent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…One study reported fewer exacerbations in the AKL1 group but the difference was not significant. In a three‐arm study of two TMs for mild‐moderate asthma there were no significant differences between groups . The mean change in asthma attacks in the 12‐week study of children was significant in favour of the TM.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…One study reported fewer exacerbations in the AKL1 group but the difference was not significant. In a three‐arm study of two TMs for mild‐moderate asthma there were no significant differences between groups . The mean change in asthma attacks in the 12‐week study of children was significant in favour of the TM.…”
Section: Resultsmentioning
confidence: 89%
“…Two participants in a TM group had abnormal liver enzymes . Three had abnormal liver function after treatment (TM 2/C1) . There was no mention of interactions between TMs and conventional medications in any study.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations